The Association Between Parental Incarceration During Childhood and Mental Health Diagnoses in Mid-Life - Victoria Ward; Hannah Grace Rew; Berkeley Franz (Journal of Primary Care & Community Health)
Introduction: The U.S. has the highest number of incarcerated persons per capita, and individuals who experience parental incarceration (PI) in childhood are at increased risk for internalizing and externalizing behavioral health conditions across the life course. This study explored the relationship between PI and mental health outcomes, including diagnoses of Attention Deficit/Hyperactivity Disorder (ADHD), Post-Traumatic Stress Disorder (PTSD), and depression by mid-life. Methods: Using data from Waves IV and V of the National Longitudinal Study of Adolescence to Adult Health, we assessed whether individuals who experienced PI before age 18 had higher rates of ADHD, PTSD, and depression diagnoses in mid-life and if the gender of the parent and child moderated these outcomes. We used a cross-sectional design which included chi-square tests of independence and logistic regression. Results: Participants who experienced PI had approximately twice the odds of depression (OR = 1.64; 95% CI: 1.30-2.09) or PTSD (OR = 1.70; 95% CI: 1.19-2.42). Parental incarceration was not a significant predictor of ADHD. There was no evidence for a differential impact of PI based on the parent or participant’s gender. Conclusion: PI is associated with negative effects, including higher rates of depression and PTSD, through mid-life. This same relationship did not exist for ADHD and gender did not moderate the relationship between PI and mental health outcomes. These findings extend knowledge on the possible long-term harms of criminal justice involvement, and are especially important for communities disproportionately affected by incarceration in the United States.